APPLICATION OF KNOWLEDGE MANAGEMENT IN THE IMPLEMENTATION OF INFORMATION SERVICES IN LIBRARIES - Brian Setyaputra Pratama; Ardhista Bhaskara Putra; Zulfatun Sofiyani (Progam Studi Ilmu Perpustakaan UIN Sumatera Utara Medan, 2026)
Information services are an interactive process designed to help users find, understand, and use information according to their needs. In the context of libraries, information services should not only provide access, but also ensure that the information is appropriate and relevant to the development of knowledge and changes in user needs. The development of information technology and the increasing use of social media have accelerated the circulation of information, while at the same time posing new challenges for libraries to continue to provide up-to-date, focused, and accountable services. This situation has forced libraries to implement knowledge management as a way to manage institutional knowledge, librarian experience, and various information sources so that they can be used optimally in their services. This study aims to determine how knowledge management is applied in library information services as a strategy to deal with changes caused by the development of information technology. The method used in this study is the Systematic Literature Review (SLR) method. The SLR method is used to find, analyze, assess, and understand all existing research related to interesting phenomena, with specific research questions related to knowledge management and library information services. The results of the study indicate that knowledge management is carried out through information sharing activities between librarians, recording work experiences, using social media to disseminate information, and processing data on user information needs. This application helps librarians better understand what users need, encourages service innovation, and strengthens the relevance of available collections and information content. The results of this study indicate that knowledge management can be used as a strategic approach to improve library information services in the digital age. From a theoretical perspective, this study adds insight into the integration of the concepts of knowledge management and information services. From a practical perspective, the results of this study provide a basis for developing library service programs that focus on knowledge sharing and information technology, so that the services provided become more flexible, responsive, and suited to changing user needs.